The Importance of Cost Structure for the Effectiveness of State Aid - Jannis Bischof; Christopher Karlsson; Davud Rostam-Afschar; Thomas Simon (Wirtschaftsdienst)
Abstract For many firms, the coronavirus crisis has lead to persistent sales slumps that generated urgent liquidity demand — unless fixed costs were reduced. The authors use a newly developed classification procedure that makes the cost structure of companies and, thus, their sensitivity to sales shocks visible. This is useful for designing effective relief measures that preserve corporate structures by protecting employment and avoiding insolvencies of companies with healthy prospects for a recovery during the post-crisis period. Such an approach helps to accelerate economic recovery.